Identification of Drugs in Parenteral Pharmaceutical Preparations from a Quality Assurance and a Diversion Program by Direct Analysis in Real-Time AccuTOFTM-Mass Spectrometry (DART-MS). (20th September 2016) - Poklis, Justin L.; Mohs, Amanda J.; Wolf, Carl E.; Poklis, Alphonse; Peace, Michelle R.
Abstract : In healthcare settings drug diversion and impairment of physicians are major concerns requiring a rapid and efficient method for surveillance and detection. A Direct Analysis in Real Time ion source coupled to a JEOL AccuTOF TM time-of-flight mass spectrometer (DART-MS) method was developed to screen parenteral pharmaceutical formulations for potential drug diversion. Parenteral pharmaceutical formulations are also known as injectable formulations and are used with intravenous, subcutaneous, intramuscular and intra-articular administration. A library was created using the mass spectra data collected by a DART-MS operated in switching mode at 20, 60 and 90 V settings. This library contained 17 commonly encountered drugs in parenteral pharmaceutical formulations that included the surgical analgesic: fentanyl, hydromorphone and morphine; anesthetic: baclofen, bupivacaine, ketamine, midazolam, ropivacaine and succinylcholine; and a mixture of other drug classes: caffeine, clonidine, dexamethasone, ephedrine, heparin, methadone, oxytocin and phenylephrine. Randomly selected 200 de-identified parenteral pharmaceutical formulations containing one or more drugs were submitted for analysis to the FIRM Toxicology Laboratory at Virginia Commonwealth University Health and were screened using the DART-MS. The drug contents of the de-identified formulations were previously confirmed by a published high performance liquid chromatography (HPLC) method. The drugs in the formulations were rapidly and successfully identified using the generated library. The DART-MS and HPLC results were in complete agreement for all 200 parenteral pharmaceutical formulations.